Adherence with single-pill amlodipine/atorvastatin vs a two-pill regimen - Bimal V Patel; R Scott Leslie; Patrick Thiebaud; Michael B Nichol; Simon SK Tang; et al (Vascular Health and Risk Management, 2008)
Bimal V Patel1, R Scott Leslie1, Patrick Thiebaud1, Michael B Nichol2, Simon SK Tang3, Henry Solomon3, Dennis Honda3, JoAnne M Foody41MedImpact Healthcare Systems, Inc., San Diego, CA, USA (Patrick Thiebaud was an employee of MedImpact Healthcare Systems, Inc. at the time the study was conducted; he is currently employed by Pfizer Health Solutions); 2University of Southern California, Los Angeles, CA, USA; 3Pfizer Inc, New York, NY, USA; 4Yale University, New Haven, CT, USA (JoAnne Foody was affiliated with Yale University at the time the study was conducted; she is currently affiliated with Harvard Medical School, Boston, MA, USA)Abstract: While clinical trials demonstrate the benefits of blood pressure and cholesterol reduction, medication adherence in clinical practice is problematic. We hypothesized that a single-pill would be superior to a 2-pill regimen for achieving adherence. In this retrospective, cohort study based on pharmacy claims data, patients newly initiated on a calcium channel blocker (CCB) or statin simultaneously or within 30 days, regardless of sequence, were followed (N = 4703). Adherence was measured over 6 months as proportion of days covered (PDC). At baseline, mean age was 63.0 years, 51.6% were female, and mean number of other medications was 7.8. Overall, 16.9% of patients were on single-pill amlodipine/atorvastatin, 15.6% amlodipine + atorvastatin, 24.7% amlodipine + other statin, 13.9% other CCB + atorvastatin, 28.9% other CCB + other statin. Percentages of patients achieving adherence (PDC ≥ 80%) were: 67.7% amlodipine/atorva statin; 49.9% amlodipine + atorvastatin; 40.4% amlodipine + other statin; 46.9% other CCB + atorvastatin; 37.4% other CCB + other statin. After adjusting for treatment selection and cohort differences, odds ratios for adherence with amlodipine/atorvastatin were 1.95 (95% confidence interval [CI], 1.80–2.13) vs amlodipine + atorvastatin, 3.10 (95% CI, 2.85–3.38) vs amlodipine + other statin, 2.06 (95% CI, 1.89–2.24) vs other CCB + atorvastatin, 2.85 (95% CI, 2.61–3.10) vs other CCB + other statin (all p < 0.0001). Single-pill amlodipine/atorvastatin may provide clinical benefits through improving adherence, offering clinicians a practical solution for cardiovascular risk management.Keywords: amlodipine besylate, atorvastatin calcium, adherence, persistence